1184. Resistance Patterns and Susceptibility Analysis of Klebsiella pneumoniae Infections in Service Members Who Sustained Trauma in Iraq and Afghanistan. (26th November 2018) - Kiley, John; Mende, Katrin; Kaiser, Susan J; Carson, Leigh; Lu, Dan Z; Merritt, Teresa; Whitman, Timothy; Petfield, Joseph L; Tribble, David R; Blyth, Dana M
Abstract: Background: Klebsiella pneumoniae was the third most common species of multidrug-resistant (MDR) Gram-negative organism in military trauma patients injured in Iraq and Afghanistan (2009–2014). This study aims to characterize the antimicrobial susceptibility and resistance patterns of K. pneumoniae isolates in these patients. Methods: All infecting K. pneumoniae isolates (IKpI) archived by the Trauma Infectious Disease Outcomes Study (TIDOS) and 96 colonizing isolates (CKpI) from groin swabs were included (6/09-12/14). All CKpI linked with IKpI were included; the remainder to total 50 MDR and 46 non-MDR CKpI were chosen randomly. Antimicrobial identification and susceptibilities were determined by CLSI criteria using the BD Phoenix Automated Microbiology System. MDR was defined as either resistance to ≥3 classes of aminoglycosides, β-lactams, carbapenems, and/or fluoroquinolones or production of an ESBL or KPC. Results: Of 588 K. pneumoniae archived isolates, 237 isolates were included in the analysis (141 IKpI and 96 CKpI). IKpI sources were 40% wound, 22% respiratory, 20% blood, 9% urine, and 9% other. Antibiotic susceptibilities for IKpI were: cefazolin (CFZ) 20%, ceftriaxone 30%, levofloxacin 62%, piperacillin–tazobactam (PTZ) 41%, meropenem 96%, and amikacin 89%. MDR IKpI and CKpI were more likely to have had prior fluoroquinolone (82% vs. 18%, P < 0.01) or anti-pseudomonal penicillin (53% vs. 47%, P < 0.01) exposure. Seventeen patients had CKpI cultured at a median of 5 days (IQR 2–17) before a subsequent IKpI with 11 (65%) having MDR CKpI. All IKpI isolated after MDR CKpI were also MDR. Among IKpI recovered after non-MDR CKpI, new resistance was noted in 1 IKpI to gentamicin (200 days post-CKpI), 1 IKpI to ertapenem (7 days post-CKpI), two IKpI to CFZ (10 days and 17 days, respectively), and 1 IKpI to PTZ (19 days post-CKpI). Serial isolates of IKpI had similar MDR status (63% initial IKpI were MDR, whereas 76% of subsequent IKpI were MDR). Conclusion: K. pneumoniae isolates in military trauma patients from Iraq and Afghanistan had challenging resistance patterns. Prior exposure to fluoroquinolones and anti-pseudomonal penicillins were associated with MDR K. pneumoniae isolation. MDR status of CKpI predicted subsequent IKpI MDR status. Disclosures: All authors: No reported disclosures.